Pengembangan Modul Pembelajaran Perakitan Komputer Berbasis Multimedia Interaktif - Bakrina Siddik; Yosi Nur Kholisho (Universitas Hamzanwadi, 2019)
This study aims to determine the feasibility of interactive multimedia-based computer assembly learning modules for class X in SMKN 1 Sikur , to test the effectiveness of interactive multimedia-based computer assembly learning modules in students class X at SMKN 1 Sikur, and knowing the response of students to the interactive multimedia-based computer assembly learning module for class X in SMKN 1 Sikur. This research is Research and Development research with ADDIE development model, namely; Analysys, Design, Development, Implementation, and Evaluation. The assessment instrument of interactive multimedia-based learning modules is in the form of a 5-scale questionnaire. The sources of research data were 2 media experts, 2 material experts, and 30 class X majoring in SMKN 1 Sikur. The results of the feasibility test of media experts from 2 aspects are categorized as very feasible with a total percentage of feasibility of 84.5%. And the results of the feasibility test from material experts from 3 aspects are categorized as very feasible with a total percentage of feasibility of 87%. Whereas based on the responses of students in class X towards the interactive multimedia-based learning module developed was feasible with a total percentage of 78%.